Bamboo as an eco-friendly material for use in aquaculture industry in Malaysia - Razak Wahab; Othman Sulaiman; Hashim W.Samsi; Mohd Shafiq Aminuddin; Izyan Khalid (Canadian Center of Science and Education (CCSE), 2008)
Aquaculture industry has contributed 10% which equal to 1,400 metric ton of the overall fish production in Malaysia. It has undergone a transition stage from small scale family oriented business to large scale operations managed by corporate bodies. Currently, the cost of constructing the basic structure of a floating cage using plastic drums or other foreign materials which is considered as a non-environmental friendly is rather expensive. This also means that such business ventures would not be affordable by the rural community. With the introduction of bamboo as the material in constructing floating cages, cost could be reduced and maintenance should be made much easier. Rural community is expected to benefit from this cost-saving material by setting up aquaculture business through village cooperatives. This paper outlines the concept of using bamboo as the main building material in the fishing industry. The cost and benefit of substituting foreign material with bamboo is examined too.